Barriers encountered during the implementation of a policy guideline on the vaccination of health care workers during the 2013–2014 measles outbreak in the Netherlands: a qualitative study. (December 2015) - Borggreve, Stephanie; Timen, Aura
Abstract Background In 2013 the Netherlands faced a measles epidemic, during which more than 2600 individuals were infected, including 19 health care workers (HCW). Vaccinating health care workers can lead to benefits on both the individual and public health level, underscoring the need for HCW vaccination. In June of 2013 the Dutch National Institute for Public Health and the Environment (RIVM) developed a measles guideline (MG) that advised Dutch hospitals to strengthen their policies concerning measles vaccination of HCWs. A key problem with guidelines, however, is adherence, which can be due to several barriers. The objective of this research was to identify the barriers that Dutch hospital professionals encountered during the implementation of this policy guideline, in order to improve the implementation of similar policies in the future. Methods In-depth interviews (n = 9) were conducted with 12 hospital health care professionals involved with prevention and control of communicable diseases. These participants represented ten different Dutch hospitals located in eight of the twelve different provinces. Participants were asked about their experiences during the 2013–2014 measles epidemic regarding infection prevention measures, including vaccination of HCWs, with a specific focus on barriers to the implementation of the RIVM guideline. Results The implementation of the MG was impeded by several (types of) barriers. First, barriers were found related to knowledge and attitude, and included lack of agreement, barriers associated with leadership and issues related to evidence-based decision making. Second, barriers related to characteristics of the guideline, mostly related to unclear or missing guideline content. Finally, contextual and social factors such as human and financial resources, belief systems, physical facilities and technical support, and national views on vaccination policies also play an important role in policy implementation. Conclusions This study has provided valuable insights into the barriers infection prevention specialists encounter during the implementation of new policies concerning vaccination of HCWs in times of a major outbreak. Moreover, this study exposed the complexity and breadth of barriers that are of importance when implementing vaccination policies in the hospital setting. In order to improve the implementation of similar policies in the future, guideline developers and health care providers and administrators alike should aim to eliminate or minimise these identified barriers by taking into account the suggestions made by the authors.